Kesadaran tentang identitas nasional pada generasi Z di era digital - Diniya, Nur Afidatul (Maliki Interdisciplinary Journal, 2025)
One form of advancement in information technology is the proliferation of social media. The use of social media today has had a considerable impact. Digital advances are changing the way people interact and participate, especially for young people or Generation Z who live in a physical and virtual world. Easy access to global information and openness to foreign cultures have the potential to enrich their horizons, but also bring negative impacts in the form of identity crises, weakened sense of nationalism, and decreased attachment to local culture. As a generation that has grown up with technology, Generation Z faces challenges and opportunities related to national identity. The influx of foreign culture has weakened civic education and weakened national identity. This research was conducted using a literature review method that focuses on collecting data from various reliable sources such as journals, books and other reliable sources that discuss the characteristics of Generation Z, national identity, and the influence of digital media in the formation of national values. This study found that Generation Z in Indonesia has a unique character that is open, creative, critical, and yet, we are faced with complex challenges in maintaining and developing a sense of nationalism in a digital era filled with globalization and technological advances. The onslaught of foreign culture and weak civic education are the main factors that weaken the sense of nationalism. However, there are positives to be seen and digital media also opens up a great opportunity to regenerate national awareness through relevant, inspiring and contextual content.